Contrasting sonochemical with electrochemical and catalytic processes for degrading representative pharmaceuticals in synthetic urine – Treatment of binary mixtures, theoretical calculations, and life cycle assessment (2025)
Active pharmaceutical ingredients (API) in urine are recognized as a primary source of environmental contamination. Thereby, the effective treatment of urine could limit the pollution by pharmaceuticals. Herein, three advanced oxidation processes (a sonochemical, a catalytic, and an electrochemical system) to deal with API in synthetic fresh urine were contrasted. Acetaminophen, losartan, and levofloxacin were considered as representative pharmaceuticals. Effects of operational parameters and the main species responsible for API removal were established. API degradation at a frequency of 582 kHz in the sonochemical process was favored, while 500 µmol L−1 of H2O2 and 90 µmol L−1 of Fe2+ were proper conditions for the catalytic process (Fenton). In turn, a low current (9 mA) and the presence of NaCl led to good degradation by the electrochemical process employing a BDD anode. Also, it was found that HO• played the principal degrading role in the three systems. Theoretical calculations allowed for the identification of the moieties on the API susceptible to transformations by HO•. The treatments in the urine matrix showed that the sonochemical system was more selective than Fenton and electrochemical processes for degrading API. The treatment of binary mixtures of API in urine evidenced more superiority and selectivity of sonochemistry for degrading hydrophobic pharmaceuticals. The sonochemical process transformed API into simple structures having less phytotoxic effects than the parent pharmaceutical or initial by-products. Moreover, a brief life cycle analysis on sonochemical treatment revealed that the highest environmental impact is attributed to the electricity required for operating the ultrasound.